Nerve Conduction Study of Newly Diagnosed Type 2 Diabetic Patients and Its Correlation with Glycosylated Hemoglobin (HbA1c) - Akter, Sanzida; Kazi Gias Uddin Ahmed; Md. Arifuzzaman; Md. Rafiqul Islam; Ahmed Hossain Chowdhury; Kanol Saha; Hashmi Sina; Iffekher Alam; Reaz Mahmud; Humayun Kabir Sarker; et al. (Bangladesh Journal of Neuroscience, 2026)
Background: Peripheral neuropathy is one of the common complications of DM and may proceed by a long period of clinically silent impaired glucose tolerance, altering the nerve function by the time diabetes is diagnosed. Nerve conduction (NCS) remain the most reliable, accurate and sensitive measure for diagnosis of peripheral neuropathy. Objectives: Evaluation of nerve conduction study of newly diagnosed type -2 diabetic patients and to find out its correlation with glycosylated hemoglobin (HbA1c). Method: This is a case control study. A total 50 newly diagnosed type-2 diabetic patients within 1 month of both sex and another 50 healthy controls were studied prospectively during January 2018 to December 2019 from outpatient department of Endocrinology and advised to attend the department of Neurology of Dhaka medical college hospital. Nerve conduction study of cross limbs was performed. Blood sugar and glycosylated hemoglobin (HbA1C) were determine. Results: Motor nerve conduction parameters were more affected. Median nerve impairment in both motor and sensory nerve conduction study was statistically significant (p<0.05) between case and control group. Most abnormal parameter is CMAP of peroneal nerve 42% followed by DL of tibial (20%) and median(18%) in motor nerve conduction study whose majority of them HbA1C was >10%. Combination tibial and peroneal nerve involvements were more common 11 (22.0%), followed. In multivariate regression analysis, HbA1C significantly (p<0.05) associated with tibial F-Lat but others were not significantly associated. There were significant positive correlations with median DL (r=0.829; p=0.002), median F-Lat (r=0.814; p=0.001), Tibial DL (r=0.805; p=0.004), tibial F-Lat (r=0.832; p=0.001), median sensory DL (r=0.824; p=0.002) Conclusion: Increased HbA1c level indicative of a state of hyperglycemia is a risk factor for polyneuropathy in diabetic patients. NCS parameters are valuable for identification, future prediction of diabetic neuropathy as well as quantitative measure of its severity